Overproduction of a bifunctional thymidylate synthetase-dihydrofolate reductase and DNA amplification in methotrexate-resistant Leishmania tropica. - Coderre, J A (1983)
Leishmania tropica promastigotes that are highly resistant to methotrexate, a dihydrofolate reductase inhibitor, have been developed. Organisms resistant to 1 mM methotrexate have a 40-fold increase in dihydrofolate reductase which is associated with thymidylate synthetase, and they contain amplified regions of DNA that may be directly visualized on stained gels of restriction digests. The amplified DNA in these organisms is about 56 kilobases in length, has a copy number about 80-fold higher than that of wild-type organisms, and constitutes about 10% of the nuclear DNA. When the methotrexate-resistant L. tropica are propagated in drug-free medium, the dihydrofolate reductase-thymidylate synthetase protein and the amplified DNA decrease in a parallel fashion until they are indistinguishable from the levels in wild-type organisms. However, when these apparent revertants are again challenged with 1 mM methotrexate, enzyme overproduction and DNA amplification occur rapidly. As in mammalian cells, it appears that drug resistance in parasitic protozoa may be mediated by gene amplification.